2012
DOI: 10.4103/0019-509x.98915
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and screening practices of general dentists concerning oral cancer in Bangalore city

Abstract: These findings concerning dentists' knowledge and opinions related to oral and pharyngeal cancer suggest strongly that educational interventions for practitioners and dental students are necessary. We contend that an offering of continuing dental education programs would go a long way to enhance the prevention and early diagnosis of oral cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
30
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 17 publications
3
30
0
1
Order By: Relevance
“…The study showed that despite knowledge of dental students of the risk factors and age prone to oral cancer, only 31.5% of them fully performed oral cancer examination in their patients that is consistent with previous report [17] and similar to the results obtained within the country [18][19][20].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The study showed that despite knowledge of dental students of the risk factors and age prone to oral cancer, only 31.5% of them fully performed oral cancer examination in their patients that is consistent with previous report [17] and similar to the results obtained within the country [18][19][20].…”
Section: Discussionsupporting
confidence: 90%
“…In Kuwait only 23 percent of dentists are aware of the risk factors and stages of oral cancer detection [16]. In India on 240 dentists, 99 percent of dentists were aware of the relationship between tobacco use and oral cancer [17]. Therefore, it can be concluded that the majority of dentists around the world recognize the major risk factors but have less information on other risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Responses to questionnaire items in the practice section indicated that 94.2% of respondents in the present study referred patients with suspicious oral lesions to specialists; this was consistent with the findings of Vijay Kumar et 22,24,29,34 It should be noted that 57% of the undergraduate dental students in Kujan et al 's study believed that it was not their responsibility to encourage patients to give up smoking. 14 In the final short-form version of the questionnaire designed in the present study, the questionnaire item on the number of biopsies taken was removed; moreover, no items on the number of oral cancer examinations performed were included.…”
Section: Discussionsupporting
confidence: 87%
“…In comparison, Vijay Kumar et al reported that 59% of Indian dentists correctly responded to this question. 22 López-Jornet et al reported that short-term oral cancer knowledge scores among the general population increased following an educational intervention. 23 With regards to knowledge of the metastatic lymph node characteristics of oral cancer, 48.6% of respondents in the current study provided correct responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation